An assessment of social negotiation as a tool of local management: a case study of the Dimako Council Forest, Cameroon - Assembe-Mvondo, Samuel; Oyono, P.R. (2004)
Access to natural resource is governed by competition and conflicts all the over the world. Alternative approaches to conflict resolution require assets provided by social negotiation, mediation and other types of social tools. This paper is based on a case of conflict of access to forest and on the use of social negotiation to solve it. It shows how a facilitation process enabled village communities of East Cameroon to secure a portion of forest in the northern part of the already classified Dimako council forest. The most meaningful result of this case study is the recognition and the rehabilitation, or the validation, of a community-based tool of social negotiation known as palabre traditionnelle (traditional arrangements and mediation), not recognized until now by mainstream science, conventional methodologies, forestry experts and policy makers in Cameroon.